Learning and Assessment Portfolios: Application at Tertiary Level - Burkšaitienė, Nijolė (Acta Paedagogica Vilnensia, 2004)
The European Council in Lisbon (2000) stated that lifelong leaming is a precondition of a successful transition to knowledge-based society in which the role and relations between different types of learning - formal, non-formal and informal - are becoming particularly important. The article makes research into non-traditional methods of learning and assessment at tertiary level under the conditions of lifelong learning. The aim of this article to is to analyse available research literature related to one the most effective methods of non-traditional learning and assessment - portfolio; to reveal its innovative character and multifunctional usage; to describe its types; to present its structure and assessment criteria. In the research the methods of scientific literature and document analysis, and reflection were employed. Portfolio is an effective method in the process of transforming the traditional paradigm of teaching and creating a new paradigm of learning and is spread in all levels of education abroad, tertiary level including. It has a multifunctional nature as it may be used as a method of learning and as a method of assessment. The most effective portfolios under the conditions of lifelong learning are the process and product portfolios. They may be applied for multiple purposes: (1) as a method of learning; (2) as a method of assessment learning; (3) as a method of recognition and assessment of non-formal and informal learning. Portfolio method is not widespread at tertiary level in Lithuania today. Introducing this method for the purposes of learning, assessing learning as well as for recognizing non-formal and informal learning at tertiary level is recommended as it contributes to the creation of lifelong learning conditions at tertiary level in Lithuania.